Physical properties of technosols as evapotranspiration covers on potash tailings piles. (15th May 2022) - Bilibio, Carolina; Uteau, Daniel; Peth, Stephan; Retz, Stefanie; Schellert, Christian; Hensel, Oliver
Abstract: The covering of potash tailings piles with technosols (artificial soils) is a modern and promising method for decreasing the saline drainage of these piles. In this context, it is important to determine whether technosols have appropriate physical properties for crop growth. In evapotranspiration covers, physical properties, such as bulk density, particle size distribution, total porosity, proportion of large pores, and available water are particularly important because they allow for robust crop growth, which subsequently determines the evapotranspiration capacity. However, few studies have been performed to assess the physical properties of technosols and their ability to act as evapotranspiration covers on potash tailings piles. Therefore, the present study aims to evaluate the physical properties of four different technosols made of municipal solid waste incineration bottom ash and coal combustion residues installed on a potash tailings pile located in Heringen, Germany. The total porosity, infiltration capacity, particle size distribution, bulk density, wettability, water retention curve, pH, electrical conductivity, and water content were determined. The pH of the technosols averaged 8.5, the electrical conductivity varied from 2.8 to 3.3 mS/cm, the mean bulk density was 1.21 g/cm³, the total porosity was 52.8%, and the rate of medium pores was 13.9% of the technosol volume. On average, the coarse fraction accounted for 42% of the technosol mass, whereas the fine fraction accounted for 52% of the sand-size particles, 43% of the silt-size particles and 5% of the clay-size particles. Likewise, no wetting restrictions for the technosols were found. To conclude, the different technosols present no limitations for crop growth, although the heavy metal contents of municipal solid waste incineration bottom ash and coal combustion residues should be considered in future studies. Graphical abstract: Image 1 Highlights: The physical properties of different technosols were evaluated. The pH values were higher than the levels suggested for cultivated soils. No physical limitations for crop growth were identified. Experimental measurements indicated similar values among the treatments.